Storage studies in different brands of evaporated and sweetened condensed liquid milk product - Arellano, Ma Elena O.; Alabastro, Estrella F. (1983)
The main objective of the study was to determine some physical, chemical and microbiological changes which occur in evaporated milk and sweetened condensed milk samples during storage. Six brands of evaporated milk and six brands of sweetened condensed milk samples were subjected to objective and subjective tests. Results showed that that for both types of milk, the pH and soluble solids content did not show any definite trend during storage. The viscosity of the evaporated milk tended to initially increase and then decrease while that of sweetened condensed milk increased continuously during the six to seven months of storage period. the absorbance of both types of milk increased with prolonged storage showing marked increases at certain points in time. Microbiological examination generally showed zero counts for all evaporated milk brands and for some of the condensed milk brands. Presence of microorganisms in some of the condensed milk products could be attributed to either product microbial load or to contamination during plating. Sensory evaluation results revealed certain changes in some of the attributes of the different milk products. The color changed with time. A linear correlation between sensory scores on color and absorbance at 420 nm showed that with an increase in the absorbance reading, there was a commensurate increase in browning discoloration as observed by the panel. The consistency also had a significant linear relationship with the viscosity readings obtained objectively. The sweetness of sweetened condensed milk showed changes during storage. The general acceptability rating differed per brand and for some brands, general acceptability changed with time. Observations by the researchers revealed occurrence of fat separation and sedimentation. The cans were generally in "good" condition especially for sweetened condensed milk cans. For evaporated milk cans, corrosion started to be evident on or before the sixth month of storage. Gassiness was not observed throughout the storage period.
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Milk; Milk -- Storage